Novel Once-Weekly Omarigliptin as Effective and Well Tolerated as Once-Daily Sitagliptin in Japanese Patients - Mann, Kate (MD Conference Express, 2014)
Patient adherence to glucose-lowering medications is a major challenge in type 2 diabetes mellitus. It is thought that an effective, well-tolerated, weekly oral antihyperglycemic agent could provide better glycemic control due to increased adherence. This article examines results of the MK-3102 Phase III Clinical Trial [NCT01703221], which evaluated the safety and efficacy of the novel dipeptidyl peptidase-4 inhibitor omarigliptin compared with placebo and sitagliptin in Japanese patients with type 2 diabetes mellitus.